Pesantren dan Tantangan Globalisasi - Sidqon, Akhmad (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
In the globalization era, traditionalist moslems in Indonesia are fighting against the problems of modernism and loss of self-identity in addition to economy problem. Above all, the problem of education occupies the highest concern because of its importance in modern era. This article is intended to investigate the impacts of globalization toward the efforts of traditional school or pesantren in running the institution. More specifically, this article higlights on how Javanese pesantrens develop their curriculum as response to globalizationÂ era and to prepare future leaders of society.